Pengaruh Tawakal Terhadap Stres Mahasiswa Baru UIN Antasari Banjarmasin - Rahmadhana, Eliza (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
In today's life, students are expected to continue to be creative and further develop their own qualities so that they can develop more according to the times. Students who have just graduated from high school and then proceed to tertiary institutions will certainly find differences in learning when they are still in high school. This transition makes new students feel pressure to cause stress. To avoid stress, according to research by Anni Zulfani, et al that trust can reduce stress, so that trust can be used as a religious coping to deal with stressors. The aims of this study were: (1) to find out the level of trust in new students (2) to find out the stress level for new students (3) whether there is an influence between trustworthiness and stress on new students.The research method used is quantitative research. The population of this study consisted of 1974 and a sample of 294 students with the sampling technique using simple random sampling. The data analysis technique of this research is using a simple linear regression test. The results of the simple linear regression test obtained a significance value of 0.000 <0.05 so that the hypothesis proposed was acceptable. The results of the hypothesis test show that the value of r count is 0.456, which means that the value of the independent variable on the dependent variable has a strong influence.